ANALISA PRODUKTIVITAS DAN PENDAPATAN USAHA TANI PADI SAWAH DIDESA LAWANG AGUNG KECAMATAN KEDURANG KABUPATEN BENGKULU SELATAN - sumantri, Bambang; Fauzi, Emlan (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2006)
This reseach is intended to find out the prodictivfty level, farm income and the factors influenced productivity of wetland paddy farm. This reseach was conducted at viI/age Lawang Agung sub-district Kedurang district South Bengkulu on july and august 2005. stratified random sampling methode was used to select 62 responden. The analysis use are farm productivity, income analysis and Cobb Douglas production function. The result show that average productivfty of wetland paddy is 2620,97 kg/ha, while average income is Rp. 1.207.308, 91111aT. he result also show that factors that influenced productivfty level are seed, urea fertilizer, the distance of farm area of to the water intake and rented land basis of land utilazation. While KCI fertilizer, SP-36 fertilizer,pesticide.labor, owned land basis of land utilalazation, and share crops basis of land utilalazation were not significant.